A Case of Cytomegalovirus-Induced Oral Ulcer in an Older Adult Patient with Nephrotic Syndrome due to Membranous Nephropathy. (29th September 2020) - Sato, Shinichi; Takahashi, Masato; Takahashi, Tetsu
Abstract : We report a case of cytomegalovirus- (CMV-) induced buccal ulcer in a patient with nephrotic syndrome. An 82-year-old man with membranous nephropathy was on immunosuppressive therapy presented with an ulcer in the oral cavity and was hospitalized. Intraoral examination revealed an inflamed and painful ulcer on the left buccal mucosa. Blood test results showed CMV positivity, and histopathological examination confirmed the diagnosis. Anti-CMV therapy (ganciclovir) was initiated from the third day of hospitalization. However, he developed dyspnea on the 14th day. Computed tomography images of the chest revealed the presence of ground-glass opacities, and noninvasive positive pressure ventilation was initiated under the provisional diagnosis of pneumocystis pneumonia caused by ganciclovir-associated myelosuppression and/or steroid-induced immunocompromised state. The patient died of pneumocystis pneumonia on the 21st day. The patient had received immunosuppressive therapy for renal dysfunction. Immunocompromised patients with CMV infection should be treated with caution, as drugs for CMV may themselves cause myelosuppression, deteriorating the prognosis of the patient.